2009
DOI: 10.1523/jneurosci.4246-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

A Nanomedicine Transports a Peptide Caspase-3 Inhibitor across the Blood–Brain Barrier and Provides Neuroprotection

Abstract: Caspases play an important role as mediators of cell death in acute and chronic neurological disorders. Although peptide inhibitors of caspases provide neuroprotection, they have to be administered intracerebroventricularly because they cannot cross the blood-brain barrier (BBB). Herein, we present a nanocarrier system that can transfer chitosan nanospheres loaded with N-benzyloxycarbonylAsp(OMe)-Glu(OMe)-Val-Asp(OMe)-fluoromethyl ketone (Z-DEVD-FMK), a relatively specific caspase-3 inhibitor, across BBB. Casp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
115
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(121 citation statements)
references
References 32 publications
5
115
0
1
Order By: Relevance
“…Moreover, functional recovery and rehabilitation was not studied in order to assess the efficacy of either treatment strategies. In agreement with the results obtained in the present study, Karatas et al (6) showed that treatment before the onset of ischemia was more effective in reducing the infarct volume than treatment after the ischemic insult. Intriguingly, a very recent study showed that preinfarct intracerebroventricular treatment with amine-functionalized singlewalled carbon nanotubes could improve tolerance of neurons to ischemic injury in the middle cerebral artery occlusion stroke model (39).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Moreover, functional recovery and rehabilitation was not studied in order to assess the efficacy of either treatment strategies. In agreement with the results obtained in the present study, Karatas et al (6) showed that treatment before the onset of ischemia was more effective in reducing the infarct volume than treatment after the ischemic insult. Intriguingly, a very recent study showed that preinfarct intracerebroventricular treatment with amine-functionalized singlewalled carbon nanotubes could improve tolerance of neurons to ischemic injury in the middle cerebral artery occlusion stroke model (39).…”
Section: Resultssupporting
confidence: 94%
“…5), however this trend was not statistically significant as seen in the case of the treatment protocol before ischemic damage was induced. Similar observations of moderate therapeutic effects obtained postischemic damage induction (compared to pretreatment) have previously been reported for other therapeutic modalities (6). We therefore concluded that a neuroprotective effect could be reproducibly obtained from a single f -CNT:siCas 3 stereotactic administration before and after ET-1 induced ischemic damage, however more significant effects were obtained when the treatment was carried out prior to the ischemic insult.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Cell-penetrating peptides have long been used to deliver drugs into cellular cytoplasm, but recently, this technology has also been used to target bioactive peptides to brain tissue (32). Nanoparticles, a more recently developed technology, have also been highly successful in delivering systemically administered peptides into brain tissue at pharmacologically relevant concentrations (33). Efforts are also being made to improve the oral delivery of peptides to increase their marketability as therapeutic agents (34).…”
Section: Discussionmentioning
confidence: 99%
“…Different strategies might be useful for this purpose: (i) A first approach may be suppression of caspase by targeted delivery of small interfering RNA specifically to macrophage/ microglial cells; 101 and (ii) the development of specific nontoxic nanocarriers able to cross the blood-brain barrier and to safety release caspase inhibitors in those areas showing high microgliosis. 102 These are great technical challenges, but the new insights into the non-lethal roles of caspases in microglia certainly support that it could be worthwhile and indicate that the idea of inhibiting caspases as a therapy for neurodegenerative diseases is anything but dead.…”
Section: Perspectivesmentioning
confidence: 99%